K-12 Virtual Schools, Accreditation, and Leadership: What Are the Issues? - Trudy A. Salsberry (Educational Considerations, 2010)
When I was young, I attended my neighborhood school. It was a square brick building with three floors and was situated on a corner just five blocks from my home. That building was torn down not long ago, and I asked my family to save a brick from that building to remind me of all the experiences I had there learning to read, use math, discover other countries, understand basic scientific principles, and communicate.
Keywords: Accreditation; virtual schools; international; transregional; standards; performance; students; instructional; research; stakeholders